Effect of 4 weeks of plyometric training in the pre-competitive period on volleyball athletes` performance - Guimarães, M. P.; Silva, R. D. O.; Dos Santos, I. A.; Da Silva, G. P.; Campos, Y. A. C.; Da Silva, S. F.; De Azevedo, P. H. S. M. (Biology of Sport, 2023)
We aimed to evaluate the effect of 4 weeks of plyometric training (PT), performed in the pre competitive period, on the vertical jump performance of professional volleyball athletes. We recruited 17 professional female volleyball players (age: 19±3 years; weight: 67.2±5.50 kg; height: 1.81±0.22 m; body fat: 14.4±2.12%; squat 1RM test: 75.5±7.82 kg; training time experience: 6.2±3.4 years) to participate in four weeks of training and assessments. They were divided into an experimental group (EG = 9) and a control group (CG = 8). Both groups were submitted to friendly matches, technical, tactical and resistance training (4 weeks/~9 sessions per week), and internal load monitoring was carried out. The EG performed PT twice a week. At the beginning and end of the four weeks, jump tests were performed. The main findings are: 1) PT when incorporated into the pre-competitive period can induce greater improvements in jumping performance (EG = 28.93±3.24 cm to 31.67±3.39 cm; CG = 27.91±4.64 cm to 28.97±4.58 cm; when comparing the percentage delta, we found a difference between groups with ES of 1.04 and P = 0.02); 2) this result is observed when the training load is similar between groups and increases over the weeks, respecting the linear progression principle. Therefore, including plyometric training in the preparatory period for volleyball, with low monotony and training strain increment, is an effective strategy for further CMJ performance improvement.